Immunosuppression with monoclonal antibodies. A model to determine the rules for effective serotherapy. - Cobbold, S; Thierfelder, S; Waldmann, H (1983)
Despite the range of available T cell specific monoclonal antibodies, there are no established rules to predict which might be immunosuppressive. We here describe a series of five rat monoclonal antibodies to a defined T cell antigen (mouse Thy-1) and evaluate their ability to immunosuppress mice. When compared with rabbit anti-lymphocyte globulin, only one of these monoclonal antibodies was able to delay skin allograft rejection and eliminate antibody responses to sheep red blood cells. This antibody was immunosuppressive following intra-peritoneal administration, even though it did not eliminate all of the T cells in vivo. Two factors may be relevant in determining the immunosuppressive properties of this reagent. First, the monoclonal antibody is of the rat IgG2b sub-class, and second, the specificity of the antibody is different to the other monoclonal antibodies in that it reacts with sub-populations of peripheral T cells, thymocytes and non-T cells. In practice, this suggests that to derive suitable monoclonal antibodies for human serotherapy, one should give attention to both the subclass and the fine specificity of the antibody for the target molecule.